2017
DOI: 10.1007/s00500-017-2738-9
|View full text |Cite
|
Sign up to set email alerts
|

Adjustability of a discrete particle swarm optimization for the dynamic TSP

Abstract: This paper presents a detailed study of the discrete particle swarm optimization algorithm (DPSO) applied to solve the dynamic traveling salesman problem which has many practical applications in planning, logistics and chip manufacturing. The dynamic version is especially important in practical applications in which new circumstances, e.g., a traffic jam or a machine failure, could force changes to the problem specification. The DPSO algorithm was enriched with a pheromone memory which is used to guide the sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The authors proposed their PSO algorithm with heterogeneous (non-uniform) parameter values; the parameters are set automatically for the critical PSO parameters based on discrete probability distributions. This approach proved to be more successful compared to the original PSO with homogeneous (uniform) parameter values [ 35 ]. Genetic algorithms are also used in several cases for the DTSP such as when [ 36 ] presenting an algorithm called the extended virtual loser genetic algorithm (eVLGA) or [ 37 ] presenting a genetic algorithm that feeds on Newton’s motion equation to show how route optimization can be improved when targets are constantly moving.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors proposed their PSO algorithm with heterogeneous (non-uniform) parameter values; the parameters are set automatically for the critical PSO parameters based on discrete probability distributions. This approach proved to be more successful compared to the original PSO with homogeneous (uniform) parameter values [ 35 ]. Genetic algorithms are also used in several cases for the DTSP such as when [ 36 ] presenting an algorithm called the extended virtual loser genetic algorithm (eVLGA) or [ 37 ] presenting a genetic algorithm that feeds on Newton’s motion equation to show how route optimization can be improved when targets are constantly moving.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The combination of prioritized K-mean and genetic algorithm was used to optimize manufacturing related transportation processes [35]. Heuristic optimization methods are used in the case of NP-hard optimization problems: genetic algorithm was used to increase machine utilization, reduce throughput time and delivery delays [36,37], while discrete particle swarm optimization (PSO) was applied to solve the dynamic travelling salesman problem in chip manufacturing, where machine failure can force changes to the problem specification [38]. A typical application field of PSO is flow shop and job shop manufacturing [39] or the machine loading problem in flexible manufacturing systems, where the feeding process is generally robotized or automatized [40].…”
Section: Content Analysismentioning
confidence: 99%
“…A (homogeneous) DPSO algorithm with pheromone was proposed in our previous work [ 8 ], and this section contains only a brief description. Adaptation to a discrete space forces some changes to the original PSO algorithm designed for solving continuous optimization problems.…”
Section: Dpso With Pheromonementioning
confidence: 99%
“…Shi et al showed that the proposed algorithm is capable of solving the generalized TSP, in which the edge lengths do not satisfy the triangle inequality. The homogeneous and heterogeneous versions of the DPSO algorithm described in the present paper are based on work by Zhong et al [ 7 ] and on our previous DTSP variant [ 8 ]. In the implementation presented here, the particle position comprises a set of edges connecting TSP cities (nodes) and the corresponding probabilities of selecting the edges to the next solution (the next position of the particle).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation